Casos y cosas: semanario popular (Vol. 2, No. 63) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: ¡Amparando a los explotadores! Se aproxima una nueva época de prosperidad, Ley del embudo, De todos y para todos, Correo franco y con franqueza.

ENGLISH: Includes: amping up the exploiters! a new age of prosperity is coming, law of the funnel, Of all and for all, Franco mail and with frankness
Cases and things: popular weekly magazine (Vol. 2, No. 63)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas